Study on the sequential tsetse-transmitted Trypanosoma congolense, T. brucei brucei and T. vivax infections to African buffalo, eland, waterbuck, N'Dama and Boran cattle - Moloo, S.K.; Orinda, G.O.; Sabwa, C.L.; Minja, S.H.; Masake, R.A. (Elsevier, 1999)
Susceptibility of African buffalo, eland, waterbuck, N'Dama and Boran cattle to sequential Glossina morsitans centralis-transmitted infections of Trypanosoma congolense, T. brucei brucei and T. vivax was compared, and their possible role as reservoirs of these parasites for G. moristans centralis, G. pallidipes, G. austeni, G. brevipalpis and G. longipennis determined. The buffalo, eland, waterbuck and N'Dama controlled T. congolense parasitaemias and were able to prevent anaemia. By contrast, one Boran became severely anaemic whilst the other controlled parasitaemia and anaemia. When the above five species of Bovidae were rechallenged with T. brucei brucei they showed persistent parasitaemias but did not develop anaemia. The buffalo died of other causes. When the remaining four bovids were rechallenged with T. vivax they became infected with mixed T. vivax/T.b brucei parasites. Eland, waterbuck and N'Dama controlled parasitaemias and anaemia whereas the Boran became anaemic. Cyclical development of T. congolense occurred in G. moristans centralis when fed on the bovid hosts, with buffalo being infective for tsetse flies for a much longer period. There was no relationship between the levels of T. congolense parasitaemia in the bovid host and the resultant infeciton rates in tsetse flies. Glossina m. centralis was more susceptible than G. pallidipes to T. brucei brucei whilst G. austeni the least; G. brevipalpis and G. longipennis were refractory to the mature infection. Again there was no relationship between T. brucei brucei parasitaemia levels in the hosts and infection rates in the flies. Glossina m. centralis and G. pallidipes showed mixed T. brucei brucei/T. vivax infections whilst G. austeni, G. brevipalpis and G. longipennis became infected with T. vivax alone. Tsetse flies showed higher T. vivax infection rates when fed on the hosts with high parasitaemias than those with low parasitaemias. Thus trypanotolerant African buffalo, eland, waterbuck, N'Dama as well as some trypanosusceptible Boran cattle can serve as reservoirs of single or mixed trypanosome infections for tsetse flies. This study has also shown that the Ag-ELISA on the sera from the five bovid hosts had low sensitivity and species-specificity. Examinations of thin wet blood films and buffy coats with a phase-contrast microscope were not sensitive enough to detect the parasites on all occasions. Xenodiagnosis using mice for T. brucei brucei and T. congolense infections, and tsetse flies for all the three trypanosome sepcies were most sensitive for the detection of trypanosome infections in the bovid hosts.